A Case of HIV and Disseminated Tuberculosis: Unrecognized Co-Infection and the Importance of Early Diagnosis - Rosandy, Milanitalia Gadys; Fadli, M Luqman; Nurdiana, Farah; Kamal Hadi, Muchamad (Fakultas Kedokteran Universitas Brawijaya, 2025)
Tuberculosis (TB) is still the main cause of death in people living with HIV (PLHIV). TB preventive therapy (TPT) and ARVs can reduce morbidity, mortality, and incidence of TB in PLHIV. With the severity of the immunodeficiency, extrapulmonary TB or disseminated TB occurs more often. Disseminated TB occurs due to the hematogenous spread of Mycobacterium tuberculosis, which occurs as a result of progressive primary infection or reactivation of latent TB infection. Disseminated TB can involve many organs such as the lungs, liver, and spleen. Delays in diagnosis often occur due to non-specific clinical manifestations; thus, the diagnosis needs to be supported by radiological and microbiological examination, as well as definite histopathological diagnosis. Treatment is given according to existing therapy guidelines with a more extensive duration and regard to the patient's clinical condition.